Evaluation of Salt, Sodium, and Potassium Intake Through Bread Consumption in Chaharmahal and Bakhtiari Province - Fathollah Aalipour (Shahrekord University of Medical Sciences, 2019)
Background and aims: Bread is considered as one of the important sources of sodium in the Iranian diet and salt is the main source of sodium, which is used to produce bread. The assessment of dietary intake is a reliable method that shows nutritional problems in the community. Therefore, the purpose of this study was to evaluate the intake of salt, sodium, and potassium through bread consumption. Methods: In the present study, 451 samples of different types of bread were tested, sent to the Food Control Laboratory for health control, and the amount of salt, sodium, and potassium was determined by potentiometric and flame-photometric methods, respectively. In addition, the amounts of salt, sodium, and potassium intake were evaluated based on their average concentration in different types of bread and per capita consumption of bread. Finally, the status of salt, sodium, and potassium intake was investigated by comparing their recommended daily allowance (RDA) and sodium/potassium ratio and sodium to caloric intake. Results: Based on the results, the concentrations of salt, sodium, and potassium were 1.95%, 769%, and 108% (mg per 100 g of bread), respectively. Furthermore, per capita consumption of bread was 320 g/d and the average intake of salt, sodium, and potassium through bread consumption was 4.03 g, 1588 mg, and 223 mg/d, respectively. Moreover, 79% of sodium RDA was received through bread consumption. In these breads, the ratio of sodium to potassium, as well as that of sodium to calorie was 12.07 (mmol/mmol) and 2 mg/calories, respectively. Conclusion: In general, the results showed that the intake of sodium and salt by using bread is more than that of their RDA. Accordingly, the ratio of sodium to potassium and sodium to caloric intake is higher than the permitted limit in these conditions, which provides the basis for the incidence of cardiovascular diseases. Therefore, strong monitoring of bread producing units is necessary.